Diversity of Drosophila egg patterning: The missing tools to explore embryonic axis formation - Stott, Helen L.; Yakoby, Nir (Frontiers in Cell and Developmental Biology, 2025)
Focusing on selected model organisms to establish scientific communities and resources has greatly advanced our understanding of biological processes, including embryogenesis, and facilitated the translation of these data into developing human remedies. However, by restricting our research to a small number of model organisms, we risk overlooking the underlying mechanisms controlling animal diversity and speciation. Changes in cell signaling, protein compatibility, and genetic tinkering are often neglected due to the lack of molecular tools in non-traditional model organisms. The era of high-throughput genome sequencing, computational gene prediction, and emerging genome editing and imaging tools, offers an opportunity to explore novel mechanisms of organismal development and homeostasis. As we develop new model platforms, it is imperative to prioritize resources effectively. What criteria make an organism a “good” candidate for becoming a new model organism for exploring embryogenesis? The axis of the Drosophila embryo is set during eggshell patterning. Although species with a dorsal ridge exhibit dramatically different patterns of the dorsalization signal, epidermal growth factor receptor activation, compared to Drosophila melanogaster, the embryonic dorsal-ventral axis remains consistent. Despite the increasing number of sequenced fly species’ genomes, the experimental tools necessary to study these species are still lagging. Here, we emphasize the need to further develop genetic and molecular tools for studying nontraditional model organisms to understand complex processes like evolution of maternal contribution and correct embryonic body axis. We address current challenges in achieving these goals, such as genetic markers, selectable markers, and the efficiency of CRISPR/Cas9 mediated genomic editing.